Efectos terapéuticos del uso de la isotretinoína en formas clínicas de acné grave en pacientes que acuden al servicio de consulta externa del Hospital Manuel Ygnacio Monteros Valdivieso del IESS-Loja durante el periodo julio 2012 - julio 2013. - Merchán Camacho, Iliana Isabel (2013)
This study was based mainly in seeing the therapeutic effects of the use of isotretinoin in severe acne forms and effectiveness, in order to provide better information to patients on this drug to avoid withdrawal. It is a work of prospective, experimental, descriptive and transversal study, realized in outpatient services at Hospital Manuel Ygnacio Monteros Valdivieso, of the city of Loja. 30 patients were studied with severe acne in a clinical trial that began treatment by increasing doses isotretinoin. The clinical improvement was valued and the therapeutic effects with monthly controls were according to their degree of severity. Acne is most often presented in the masculine gender , the age group 11-20 years was the most affected , lesions occurred mainly in the face, and clinical form severe- inflamatory the more common. The therapeutic effects presented were cheilitis, xerosis , epistaxis , mood changes , joint and muscle pain , according to the lab there were isolated cases of hypertriglyceridemia, hyperlipidemia and increased liver enzymes . KEY WORDS: ACNE, ACNE CLINICAL FORMS, ISOTRETINOIN, THERAPEUTIC EFFECTS OF ISOTRETINOIN.